Sustainable Management of Calcareous Saline-Sodic Soil in Arid Environments: The Leaching Process in the Jordan Valley - Mufeed Batarseh (Applied and Environmental Soil Science)
A leaching experiment of calcareous saline-sodic soil was conducted in Jordan Valley and aimed to reduce the soil salinity ≤ 4.0 dS m−1. The quantification of salt removal from the effective root zone was done using three treatment scenarios. Treatment A contained soil amended with gypsum leaching with fresh water (EC = 1.1 dS m−1). Treatments B and C contained nonamended soil, but B was leached with fresh water only while treatment C’s soil was washed with saline agricultural drainage water (EC = 8 dS m−1) at the start of the experiment and continued with fresh water to reach the desired soil salinity. All treatments were able to reduce the soil salinity to the desired level at the end of the experiment; however, there were clear differences in the salt removal efficiencies among the treatments which were attributed to the presence of direct source of calcium ion. The soil amended with gypsum caused a substantial decline in soil salinity and drainage water’s electrical conductivity and drained the water twice as fast as the nonamended soil. It was found that utilizing agricultural drainage water and gypsum as a soil amendment for calcareous saline-sodic soil reclamation can beneficially contribute to sustainable agricultural management in the Jordan Valley.